2001
DOI: 10.1108/00070700110391470
|View full text |Cite
|
Sign up to set email alerts
|

The influence of β‐cyclodextrin on goaty flavour ‐ Characterization of synthetic inclusion complexes with capric acid and caprylicacid

Abstract: Sensory analysis shows that the addition of 0.4 per cent (w/v) of the macrocyclic bcyclodextrin (bCD) to goat's milk improves the flavour and reduces its goaty taste, due to encapsulation of molecules responsible of this flavour. In vitro studies of the inclusion of formed complexes between bCD and short-chain fatty acids, caprylic (C 8 ) and capric acid (C 10 ), were carried out by differential scanning calorimetry (DSC) and proton magnetic resonance ( 1 H NMR). Complex formation was confirmed by DSC, through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Compared with control, samples with added β-CD showed increased acceptance score ranging from 2·50 ± 0·22 to 4·51 ± 0·29 when the level increased from 0·1% to 0·9%, indicating the effective capacity of β-CD for reducing the goaty flavor. Similar results were reported by others (Meier et al 2001; Young et al 2012). The capacity of reducing goaty flavor of the yogurt (represented by score) was positively correlated to the β-CD ( P < 0·05) in the range of 0·1%–0·9% (w/v).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Compared with control, samples with added β-CD showed increased acceptance score ranging from 2·50 ± 0·22 to 4·51 ± 0·29 when the level increased from 0·1% to 0·9%, indicating the effective capacity of β-CD for reducing the goaty flavor. Similar results were reported by others (Meier et al 2001; Young et al 2012). The capacity of reducing goaty flavor of the yogurt (represented by score) was positively correlated to the β-CD ( P < 0·05) in the range of 0·1%–0·9% (w/v).…”
Section: Resultssupporting
confidence: 92%
“…Moreover, C 8 decreased most significantly, indicating the more affinity of C 8 with β-CD. These results were in accordance with those of Meier et al (2001), who proved that β-CD bound caprylic and capric acids to remove perception of goat milk flavor by differential scanning calorimetry (DSC) and proton magnetic resonance ( 1 H NMR) spectroscopy analysis. Young et al (2012) also found that β-CD bound 4-methyl branched chain fatty acids and their straight chain isomers in reducing goaty flavor intensity of yogurt.…”
Section: Resultssupporting
confidence: 92%
“…Meier and others (2001a) showed that β‐CD altered perception of goat milk flavor. They also showed that β‐CD binds octanoic and decanoic acids, implying a potential for flavor reduction if BCFAs will also form complexes, as is very likely from that sensory trial.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of β ‐CD did not represented any beneficial effect on the total concentration of carotenoids (Table 1); it is possible that the effects of the low temperatures used during the manufacturing of juices (ultra‐freezing) were much higher than those from the addition of CDs and therefore, the effects of CDs was masked. On the other hand, some studies have previously reported beneficial effects of β ‐CD on the quality of juices subjected to pasteurization and sterilization protocols (Meier et al . 2001; Rodríguez‐Amaya 2003; Jun 2009).…”
Section: Resultsmentioning
confidence: 99%